An autopsy case of HELLP syndrome with disseminated aspergillosis - Kobayashi, M; Ito, M; Hotchi, M (Nihon Ishinkin Gakkai zasshi, 2000)
Disseminated aspergillosis is an uncommon and unpredictable complication in severely immunocompromised patients and poses a challenging problem in the management and care of seriously ill patients receiving intensive care therapy. We report an autopsied case of disseminated aspergillosis occurring ina 31-year-old female patient who was treated for HELLP (hemolysis, elevated liver enzymes, and low platelet count) syndrome. She initially presented with edema and proteinuria at a pregnancy check-up. At gestational age 33 weeks and 2 days, she had right lower abdominal pain, nausea, and jaundice. The next day she delivered a male neonate transvaginally, followed by excessive postpartum uterine bleeding. Although an emergency hysterectomy was performed, her hemorrhagic diathesis could not be controlled even after transcatheter embolization of the internal iliac arteries with subsequent ligation and repeated blood transfusions totalling to 31,070 ml. She eventually died of a cerebral hemorrhage 21 days after the parturition. Autopsy showed generalized jaundice and petechiae, as well as extensive hemorrhage observed in the abdominal wall, peritoneal cavity, and retroperitoneal and pelvic spaces. In addition,there were multifocal hemorrhages found in the left temporal, right frontal and posterior lobes of the cerebrum, and pons. Disseminated aspergillosis was found in the lungs, trachea, brain, esophagus, stomach, heart, and thyroid gland. These findings suggest that systemic postoperative complications, associated with massive blood transfusions and hepatic failure, mutually contribute to the overall deterioration of host defense mechanism, and may underlie the occurrence of devastating systemic fungal infection.